A disproportionality analysis of FDA adverse event reporting system events for misoprostol - Li Yang; Wenting Xu (Scientific Reports)
Abstract Misoprostol was originally used to treat gastric ulcers, and has been widely used in abortion, cervical maturation, induced labour and postpartum hemorrhage. But there are still many undetected adverse events (AEs). The purpose of this study was to provide a comprehensive overview of the safety of misoprostol. Adverse events related to misoprostol were collected from the FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2004 to the second quarter of 2024. This study used proportional disequilibrium methods such as reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and empirical Bayes geometric mean (EBGM) to detect AEs. After analyzing 17,427,762 adverse event reports, a total of 2032 adverse events reports related to misoprostol were identified, involving 23 system organ classes and 30 preferred terms. The most common AEs were foetal exposure during delivery(n = 201), uterine tachysystole(n = 95), uterine rupture (n = 95), and heart rate decreased (n = 93). Although most AEs complied with the drug instruction, new AEs signals such as congenital aqueductal stenosis and congenital brain damage were also identified. Clinicians should make appropriate evaluation when using misoprostol, closely monitor the indicators of patients, and have appropriate countermeasures for possible adverse events.